Seconde main et deuxième vie - Octave Debary; Philippe Gabel (Mélanges de la Casa de Velázquez, 2010)
This article looks at the importance that our society attaches to the reappraisal of used objects when they reach the end of their useful life. Laid out in flea markets, displayed in museums or re-used in contemporary art, some objects, some pieces of junk, acquire recovery or exchange value. How are we to gauge the importance of their presence, particularly for these “second hand” places commonly known as flea markets? This article attempts to show that such objects possess a value deriving from their power to tell a story —a story passed from hand to hand through trade. Thus objects acquire new owners and change hands, assuring them a new future, often as memorabilia.